1992
DOI: 10.2466/pms.1992.74.3.706
|View full text |Cite
|
Sign up to set email alerts
|

Home Advantage: Does it Exist in Individual Sports

Abstract: This study examined whether the home advantage exists in individual sports. The percentage of 792 wrestling matches won at home and away were compared for a high school wrestling team from 1980–1984 A significant home advantage was found: 61% vs 54%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 2 publications
2
13
0
Order By: Relevance
“…Continuing with contact sports, in local competitions HA was established in wrestling (Gayton & Langevin, 1992) with slight effects of 61% of confrontations in favor of the local fighter and of 54% related to the visitor, establishing the comparative with the same confrontations under the location condition, in line with other findings (McAndrew, 1993). Evidence was found that pushed to confirm HA for both genders (Krumer, 2017) having control over the quality of the adversary.…”
Section: Introductionsupporting
confidence: 62%
“…Continuing with contact sports, in local competitions HA was established in wrestling (Gayton & Langevin, 1992) with slight effects of 61% of confrontations in favor of the local fighter and of 54% related to the visitor, establishing the comparative with the same confrontations under the location condition, in line with other findings (McAndrew, 1993). Evidence was found that pushed to confirm HA for both genders (Krumer, 2017) having control over the quality of the adversary.…”
Section: Introductionsupporting
confidence: 62%
“…Evidently, this officiating component is vital for home advantage in individual sports. This could explain why significant home advantage has been observed in wrestling (Gayton and Langevin, 1992), even at high school level, but not international tennis or golf Nevill et al, 1997). It would appear that the potential for biased officiating in subjectively judged events predicted by Ansorge and Scheer (1988) is confirmed in terms of home advantage.…”
Section: Discussionmentioning
confidence: 71%
“…Some evidence of home advantage has been identified in crosscountry running (McCutcheon, 1984), wrestling (Gayton and Langevin, 1992) and World Cup alpine skiing (Bray and Carron, 1993). In contrast, once quality of athlete had been accounted for, home advantage was not found to be a major influence on performance in individual 'grand slam' tennis or 'major' golf tournaments .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, no study has investigated home advantage in fencing or taekwondo isolated from other sports. Despite the low volume of publications concerning home advantage in combat sports, all of them confirmed an advantage of competing at home compared to competitions away, even when the competitions were between school wrestling teams from the same country [7,8]. The only study considering combat sports in the context of the Olympic Games [4] was conducted more than 10 years ago and included only boxing, considering data from Olympic Games between Athens 1896 and Atlanta 1996.…”
Section: Introductionmentioning
confidence: 92%
“…Despite the introduction of technological apparatuses (e.g., body protectors in taekwondo, video replay in judo) to decrease refereeing errors in combat sports, referees still have an important influence in the outcome of these sports, as they can stop the combat in specific moments, affecting the match outcome. Few studies have investigated home advantage in combat sports, including boxing [5], judo [6], wrestling [7,8], and only one study [4] considered a combat sport during the Olympic Games. Moreover, no study has investigated home advantage in fencing or taekwondo isolated from other sports.…”
Section: Introductionmentioning
confidence: 98%